Impact of transsexualizing process centers on self-medication of transgender individuals - Arthur Machado Geiger Dias de Moraes; Caren Nariel Pereira Santos Souza; Luiza Taddeo Marques; João Fernando Nascimento de Barcelos; Felipe Barros Oliveira; Rafaela Góes Bispo; Rodrigo Gomes Santos; Ailton da Silva Santos; José Antônio Diniz Faria Júnior; Luciana Mattos Barros Oliveira (Universidade de São Paulo, 2024)
ABSTRACT OBJECTIVE The transgender population in Brazil faces marginalization and difficulties in accessing education and health, leading many individuals to self-medicate. This study aimed to evaluate the impact of the implementation of Specialized Centers in the Transsexualizing Process (SCTP) on the use of cross-sex hormone therapy (CSHT) without medical prescription, as well as the level of education and mental health profile of these individuals. METHODS This is a cross-sectional study with data from physical and electronic medical records between September 2017 and February 2023 regarding the use of CSHT before and after the implementation of two SCTP in the state of Bahia, Brazil, in addition to data on education level, previous diagnosis of anxiety and depression of patients. RESULTS A total of 219 participants, 127 transgender men (TM) and 92 transgender women and travestis (TrTW), were assessed. A significant reduction in the prevalence of self-medication was observed in both TrTW (92.98% before and 51.43% after, p<0.001), and TM (47.17% before and 25.67% after, p = 0.010) with the implementation of SCTP. Transgender individuals who used CSHT before accessing the service were found to have a lower prevalence of depression. Self-medication was not significantly associated with education or anxiety in our sample. CONCLUSION The results indicate the need for the expansion of SCTP, as they were associated with lower rates of self-medication in the transgender population.